2001
DOI: 10.1007/s005200100253
|View full text |Cite
|
Sign up to set email alerts
|

Oral health and quality of life among patients with head and neck cancer or haematological malignancies

Abstract: The aim of the present study was to monitor the health-related quality of life (HRQOL) of patients with head and neck cancer or haematological malignancies during a period from before to after medical treatment, and to investigate the relationships between patient experiences of oral symptoms and HRQOL. The sample consisted of 41 consecutive patients. At the start, during and end of radiotherapy or the second/third cycle of chemotherapy, patients rated their experiences of oral symptoms on a 100-mm visual anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 43 publications
5
33
0
5
Order By: Relevance
“…This study confirms previous observations that malnutrition has a negative impact on QoL (Ovesen et al, 1993;Larsson et al, 1995;Ohrn et al, 2001), although this was not observed by Hammerlid et al (1998). Small et al (2002) suggest that, as well as providing a global assessment of the patient's nutritional status, the scored PG-SGA can also be used to evaluate nutritional QoL.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study confirms previous observations that malnutrition has a negative impact on QoL (Ovesen et al, 1993;Larsson et al, 1995;Ohrn et al, 2001), although this was not observed by Hammerlid et al (1998). Small et al (2002) suggest that, as well as providing a global assessment of the patient's nutritional status, the scored PG-SGA can also be used to evaluate nutritional QoL.…”
Section: Discussionsupporting
confidence: 90%
“…The impact of nutrition on QoL has not been well documented, however there are several studies that have observed poorer QoL outcomes in malnourished patients when compared with well-nourished patients (Ovesen et al, 1993;Larsson et al, 1995;Ohrn et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…cooking, socialising, enjoying life/work) for the majority of patients. Similarly, symptoms specific to head and neck cancer, like taste and smell changes, dry mouth, sticky saliva, and coughing were significantly worse than pretreatment scores and have been described previously 63 . At this early stage, Örhn et al 63 found 56% of patients reported that their oral symptoms had been a hindrance to everyday life, reflecting the global swallowing score found in the current AFRT-CB group.…”
Section: Four To Six Weeks Post-treatmentsupporting
confidence: 77%
“…The detrimental consequences of this malnutrition are diverse: poor prognosis, morbidity, decreased quality of life and clinical management of patients, but also anorexia (Bernstein, 1978;Andreyev et al, 1998;Berteretche et al, 2004). Taste changes, which are among the most common chemotherapy-associated side effects (Ravasco, 2005), are not only distressing for patients and impact on their quality of life (Epstein et al, 1999 and2002;Ohrn et al, 2001), but also lead to food aversions and reduced food intake (Ravasco, 2005). …”
Section: Characteristics and Development Of Preferences And Aversionsmentioning
confidence: 99%